(3GddeYjI GdSfjI aj JMbjb GdEdbGA aj GdCefjIs - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3CeG HYO abO SCdJ CjOc Gddg JYGdi CjgG GdCN Yf eSFdI GdZQGfjb GdeTghQI hPcQJ Cf GdYdeGA CWGdhG ai GdCLhHI YfgG HYO EKHGJ s
(3BNQgG (B:s
(3Udi Gddg Ydjg hSde ai cd eG jCJi Hg hfOQ GdeMJhi Ydi bhdg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
Keywords: (3GdeLGejYs